Inactivation of the Bacterial RNA Polymerase Due to Acquisition of Secondary Structure by the ω Subunit - Sarkar, Paramita (American Society for Biochemistry and Molecular Biology, 2013)

(untitled)
The widely conserved ω subunit encoded by rpoZ is the smallest subunit of Escherichia coli RNA polymerase (RNAP) but is dispensable for bacterial growth. Function of ω is known to be substituted by GroEL in ω-null strain, which thus does not exhibit a discernable phenotype. In this work, we report isolation of ω variants whose expression in vivo leads to a dominant lethal phenotype. Studies show that in contrast to ω, which is largely unstructured, ω mutants display substantial acquisition of secondary structure. By detailed study with one of the mutants, ω(6) bearing N60D substitution, the mechanism of lethality has been deciphered. Biochemical analysis reveals that ω(6) binds to β′ subunit in vitro with greater affinity than that of ω. The reconstituted RNAP holoenzyme in the presence of ω(6) in vitro is defective in transcription initiation. Formation of a faulty RNAP in the presence of mutant ω results in death of the cell. Furthermore, lethality of ω(6) is relieved in cells expressing the rpoC2112 allele encoding β′(2112), a variant β′ bearing Y457S substitution, immediately adjacent to the β′ catalytic center. Our results suggest that the enhanced ω(6)-β′ interaction may perturb the plasticity of the RNAP active center, implicating a role for ω and its flexible state.